Automated determination of red cell methaemoglobin reductase activity by a continuous-flow system for screening hereditary methaemoglobinaemia. Issue 6 (June 1979) - Tanishima, K; Fukuda, N; Takeshita, M; Takizawa, Y; Kitamura, T; Yoneyama, Y
Abstract : A flow diagram for the automated determination of ferricyanide reductase activity in red blood cells was prepared in the modules from AutoAnalyzer AA I (Technicon Instruments Inc). Ferricyanide reductase assay can be substituted for assay of cytochrome b5 reductase (EC 1.6.2.2), which plays a major role in reducing methaemoglobin in erythrocytes, and is defective specifically in the erythrocytes of patients with hereditary methaemoglobinaemia. The effective sampling rate of the analysis is 30/h, and less than 0.05 ml of whole blood is required. Interference of haemoglobin with absorption by potassium ferricyanide at 420 nm is effectively exculded by dialysis. This automated method was compared with the accepted diaphorase method, and it distinguished clearly the ferricyanide reductase activity of cord bloods from that of adult bloods. The activity of the blood from a patient with hereditary methaemoglobinaemia was only residual. It is suggested that the method is useful as a mass screening test for hereditary methaemoglobinaemia.